Acquired Moebius-like palsy in uncontrolled diabetes: An uncommon manifestation of a common metabolic disease - Singh, Dr.Avi; SHARMA, DR. DEEPAK; Srivastava, Dr. Saurabh (Indian Journal of Case Reports, 2026)
We report the case of a 58-year-old woman with poorly controlled type 2 diabetes mellitus who presented with acute horizontal binocular diplopia due to isolated right abducens nerve (cranial nerve VI) palsy. Laboratory evaluation revealed severe hyperglycemia with glycated hemoglobin of 15.8%. She improved significantly after structured glycemic optimization. This case highlights a rare but reversible presentation of diabetic cranial mononeuropathy.